Investigation the global effect of rare earth gadolinium on the budding Saccharomyces cerevisiae by genome-scale screening - Cao, Yuhang; Zhang, Caiyun; Fang, Yu; Liu, Yumeng; Lyu, Kexin; Ding, Jian; Wang, Xue (Frontiers in Microbiology, 2022)
The rare earth gadolinium (Gd) is widely used in industry and medicine, which has been treated as an emerging pollutant in environment. The increasing pollution of Gd has potential hazards to living organisms. Thus it is essential to investigate the toxicity and action mechanism of Gd in biological system. In this study, the global effect and activation mechanism of Gd on yeast were investigated by genome-scale screening. Our results show that 45 gene deletion strains are sensitive to Gd and 10 gene deletion strains are Gd resistant from the diploid gene deletion strain library of Saccharomyces cerevisiae. The result of localization analysis shows that most of these genes are involved in cell metabolism, cell cycle, transcription, translation, protein synthesis, protein folding, and cell transport. The result of functional analysis shows that four genes (CNB1, CRZ1, VCX1, and GDT1) are involved in the calcium signaling pathway, and four genes (PHO84, PHO86, PHO2, and PHO4) are involved in phosphorus metabolism. For Gd3+ has the similar ion radius with Ca2+ and easily binds to the phosphate radical, it affects Ca2+ signaling pathway and phosphorus metabolism. The genes ARF1, ARL1, ARL3, SYS1, COG5, COG6, YPT6, VPS9, SSO2, MRL1, AKL1, and TRS85 participate in vesicle transport and protein sorting. Thus, Gd accumulation affects the function of proteins related to vesicle transport, which may result in the failure of Gd transport out of cells. In addition, the intracellular Gd content in the 45 sensitive deletion strains is higher than that in the wild type yeast under Gd stress. It suggests that the sensitivity of yeast deletion strains is related to the excessive intracellular Gd accumulation.